Diabetes‐specific emotional distress in people with Type 2 diabetes: a comparison between primary and secondary care. Issue 10 (20th May 2014) - Stoop, C. H.; Nefs, G.; Pop, V. J.; Wijnands‐van Gent, C. J. M.; Tack, C. J.; Geelhoed‐Duijvestijn, P. H. L. M.; Diamant, M.; Snoek, F. J.; Pouwer, F.
Abstract Aims To compare levels of diabetes distress in people with Type 2 diabetes treated in primary and secondary care and to examine demographic and clinical correlates that may explain potential differences in levels of distress between care settings. Methods People with Type 2 diabetes from 24 primary care practices (n = 774) and three secondary care clinics (n = 526) completed the Problem Areas In Diabetes questionnaire. Data on HbA1c levels and diabetes complications were derived from medical charts. Hierarchical ordinal regression analysis was used to investigate which correlates could explain the potential differences in level of diabetes distress between care settings. Results Diabetes distress levels and the prevalence of elevated diabetes distress were considerably lower in the participants treated in primary care (mean (sd) total diabetes distress score 8 (11); 4% of participants with a Problem Areas In Diabetes score ≥ 40) than in secondary care (mean (sd) total diabetes distress score 23 (21); 19% of participants with a Problem Areas In Diabetes score ≥ 40, P < 0.001). In addition to care setting, the following variables were also independently related to diabetes distress: younger age, ethnic minority status, using insulin, having a higher HbA1c level, having a higher BMI and the presence of neuropathy. Other diabetes complications were not independently associated with diabetes distress. Conclusions In primary care, lower levels of diabetes distress were reported than in secondary care. The difference in diabetes distress between care settings can be largely, but not fully, explained by specific demographic and clinical characteristics. These results need to be interpreted with caution as they are based on two separate studies, but do call into question the need to screen for diabetes distress in people with Type 2 diabetes in primary care.